Strengthening economic relations between Ukraine and Poland in the context of external threats from the Russian Federation - Lymar, Valeriia; Zabolotnyy, Serhiy (Turystyka i Rozwój Regionalny, 2023)
This study aims to identify the preconditions for deepening economic relationsbetween Ukraine and Poland. It is determined that these countries have a common historicaland cultural basis for cooperation. Poland was the first country to help Ukraine after Russia’sfull-scale invasion on February 24, 2022. The main purpose of the research is to analyze theinstitutional and contractual dimensions of the strategic partnership between Poland andUkraine, the legal framework for economic cooperation, international trade, and investmentactivity, and elaborate on proposals to develop the relations between the two countries.Based on the analysis, the authors present several recommendations for further deepeningeconomic cooperation between Ukraine and Poland in the context of external threats fromthe Russian Federation.